Transgresje nowoczesności - Pieniążek, Paweł (Kultura i Społeczeństwo, 2018)
The author considers the possibility of transgression in the contemporary world in the context of attempts to treat sexaholism as such. He questions the justifiability of using the term “transgression” and refers to its earlier meaning in the ideas of Georges Bataille and in post-structuralism.